Review of Rainfall Hourly Distributionon the Island of Java - Sri Harto Brotowiryatmo (Journal of the Civil Engineering Forum, 2016)
Rainfall hourly distribution is still a very important variable in the computation of the design of some hydraulic works. It has been generally known that this distribution will defer from one to the other region. The distribution defers from that exist in this area may invite additional inaccuracy in further analysis. This review presents some works which have been done in these last years, to fulfill the absence of this distribution on the island of Java region.Keywords: telemetry system; rainfall intensity; information spreading